Construction and Overall Protection of Ecological and Marine Cultural Composite Landscape Network in Quanzhou, Fujian - Dongfang LU; Yaru ZHENG; Tianteng HAN; Shunhe CHEN (Fengjing Yuanlin)
ObjectiveCoastal cities are susceptible to both internal and external factors, making them difficult to recover under the frequent influence of human activities. These factors collectively contribute to the vulnerability of marine ecosystems, posing numerous challenges for the protection and construction of coastal cities in terms of ecology, culture, and environment. Among these challenges, the imbalance of ecological and cultural resources stands out prominently. This research aims to explore the construction of an ecological and marine cultural composite landscape network, so as to promote the coupling and coordination between marine culture and the ecological environment, and optimize the allocation of ecological and marine cultural landscape resources. This will not only protect important ecological resources and cultural habitats but also strengthen the connections between them.MethodsIntegrated application of MSPA, landscape connectivity evaluation, MCR model, K-means clustering, Linkage Mapper, and cultural corridor spatial pattern model enable the construction of ecological network and marine-cultural network for the research area. The coupling of the aforesaid ecological network and cultural network forms a composite landscape network pattern. An evaluation indicator system for the coupling degree of ecological and cultural functions is constructed, and the entropy weight method is used to calculate index weights and the coupling coordination degree. Functional evaluations and hierarchical optimizations of the composite landscape network are conducted.ed on the evaluation results of the gravity model, these corridors are classified into first-class, second-class, and third-class corridors, forming the spatial pattern of the Quanzhou ecological network.ResultsThe MCR model identifies 136 potential ecological corridors, totaling 4381.139 km. Based on the evaluation results of the gravity model, these corridors are classified into first-class, second class, and third-class corridors, forming the spatial pattern of the Quanzhou ecological network. Linkage Mapper identifies 19 cultural corridors, totaling 888.001 km, and combined with the influence scope of core cultural landscape information points, the spatial pattern of the Quanzhou cultural network is constructed. The dissemination range of cultural landscape information points is between 0.04 km and 15.19 km. The integration of the ecological and cultural networks results in a composite pattern of Quanzhou’s marine cultural and ecological landscape network. Considering the corridor radiation range, a 1,000 m buffer along the composite corridor network is taken as the evaluation object for each corridor. Using the coupling coordination degree calculation formula, the coupling coordination degree of 62 corridors is calculated and classified according to the coupling coordination degree standard, forming the evaluation results of Quanzhou’s ecological and marine cultural composite landscape network. The results indicate that 1 corridor is severely imbalanced, 16 moderately imbalanced, 32 basically balanced, 11 moderately balanced, and 2 in excellent balance.ConclusionThe regional comprehensive coupling coordination degree of the composite corridors reveals a gradual decrease as the distance from coastal and central urban areas increases. The results show that the degree of coupling coordination presents the spatial characteristics of increasing from the coastal and central urban areas to the periphery. This phenomenon mainly considers the following two factors: first, the quality of the ecological environment in the northern, western and central regions is better, the ecological network coverage is complete, and the distribution of marine cultural resources is balanced; second, although the coastal and central urban areas have dense cultural heritage sites and prominent cultural values, the lack of ecological sources and urban environmental problems have led to a decrease in the coordination of their landscape corridors. Therefore, in the optimization of the complex landscape corridor, we should focus on the restoration of the ecological problems in the coastal areas and the central urban areas, and transform the cultural-oriented network into an ecological-cultural dual-function network Secondly, in the interior of the basic coordination section corridor, should focus on the ecological function and regional characteristics to enhance the cultural value. The construction and optimization strategy of Quanzhou’s ecological and marine culture composite landscape network provides a basis for the integration, flow, efficient utilization and overall protection of Quanzhou’s ecological and cultural resources, it also provides a reference template for the comprehensive coordinated protection of ecology and culture and the integrated sustainable development of coastal cities.